2021
DOI: 10.1186/s13063-021-05032-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and safety of inhaled magnesium sulphate in combination with standard treatment in patients with moderate or severe COVID-19: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives Basic and clinical studies have shown that magnesium sulphate ameliorates lung injury and controls asthma attacks by anti-inflammatory and bronchodilatory effects. Both intravenous and inhaled magnesium sulphate have a clinical impact on acute severe asthma by inhibition of airway smooth muscle contraction. Besides, magnesium sulphate can dilate constricted pulmonary arteries and reduce pulmonary artery resistance. However, it may affect systemic arteries when administered intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Magnesium sulfate 2%, a smooth muscle relaxant, exerts anti-cytokine effects, reduces airway hyperreactivity, and induces bronchodilation and vasodilation, hence improving the ventilation-perfusion mismatch. Therefore, it can be used as an adjuvant therapy to improve the patient's oxygenation (comparable to Nitric oxide) [35] , [36] . Moreover, the systemic adverse reactions of magnesium sulfate 2% could be reduced through using its nebulized form instead of the systemic forms [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnesium sulfate 2%, a smooth muscle relaxant, exerts anti-cytokine effects, reduces airway hyperreactivity, and induces bronchodilation and vasodilation, hence improving the ventilation-perfusion mismatch. Therefore, it can be used as an adjuvant therapy to improve the patient's oxygenation (comparable to Nitric oxide) [35] , [36] . Moreover, the systemic adverse reactions of magnesium sulfate 2% could be reduced through using its nebulized form instead of the systemic forms [35] , [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it can be used as an adjuvant therapy to improve the patient's oxygenation (comparable to Nitric oxide) [35] , [36] . Moreover, the systemic adverse reactions of magnesium sulfate 2% could be reduced through using its nebulized form instead of the systemic forms [35] , [36] . In our patient magnesium sulfate 2% inhalation could have improved post-extubation transient hypoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of DMB supplementation was retained after adjusting for age and hypertension. Further promising work is ongoing [ 86 – 88 ] (Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial decrease in the need for oxygen or intensive treatment assistance is reported in elderly COVID 19 patients upon the intake of vitamin D, magnesium, and vitamin B12 (DMB) in combination (Tan et al 2020). Iran's clinical trial registry (IRCT) confirmed that magnesium sulphate inhalation is effective in improving respiratory symptoms such as shortness of breath, cough and oxygen saturation in COVID 19 patients (Pourdowlat et al, 2021).…”
Section: Covid 19 and Magnesiummentioning
confidence: 99%